Imaging microstructure of the barley rhizosphere: particle packing and root hair influences. Issue 4 (20th November 2018) - Koebernick, Nicolai; Daly, Keith R.; Keyes, Samuel D.; Bengough, Anthony G.; Brown, Lawrie K.; Cooper, Laura J.; George, Timothy S.; Hallett, Paul D.; Naveed, Muhammad; Raffan, Annette; Roose, Tiina
Summary: Soil adjacent to roots has distinct structural and physical properties from bulk soil, affecting water and solute acquisition by plants. Detailed knowledge on how root activity and traits such as root hairs affect the three‐dimensional pore structure at a fine scale is scarce and often contradictory. Roots of hairless barley ( Hordeum vulgare L. cv Optic) mutant (NRH) and its wildtype (WT) parent were grown in tubes of sieved (<250 μm) sandy loam soil under two different water regimes. The tubes were scanned by synchrotron‐based X‐ray computed tomography to visualise pore structure at the soil–root interface. Pore volume fraction and pore size distribution were analysed vs distance within 1 mm of the root surface. Less dense packing of particles at the root surface was hypothesised to cause the observed increased pore volume fraction immediately next to the epidermis. The pore size distribution was narrower due to a decreased fraction of larger pores. There were no statistically significant differences in pore structure between genotypes or moisture conditions. A model is proposed that describes the variation in porosity near roots taking into account soil compaction and the surface effect at the root surface.